Islamic Law in National Legal System (Theory of Applicability, Development and Implementation in Indonesia) - Wahyudi, Trubus (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2024)
Indonesia is a country of law based on Pancasila and the 1945 Constitution of the Republic of Indonesia, upholding ethical values and moral values, as well as the noble personality of the nation, believing in and being devoted to God Almighty, and respecting diversity in social, national and state life, and protecting the dignity and honor of every citizen. The Unitary State of the Republic of Indonesia also aims to realize an orderly, clean, prosperous and orderly life in the life of the nation, state and society. ExistenceIslamic law is closely related to the Islamic religion which is always interesting to study and discuss, because the majority of the population of Indonesia is Muslim. Because Islamic law always follows and cannot be separated at all from the